Waterproof antibacterial medical polypropylene bottle cap and preparation method thereof
By combining modified titanium dioxide and carrier resin, needle-shaped nanocrystals and modified polypropylene bottle caps are formed, which solves the problem of poor antibacterial effect of polypropylene bottle caps and achieves improvements in long-term antibacterial performance and appearance quality.
Patent Information
- Application Number
- CN202411365929.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The antibacterial effect of existing polypropylene bottle caps gradually weakens after long-term use, and their durability is poor, making it difficult to effectively prevent drug packaging from being contaminated by microorganisms.
Modified titanium dioxide is used to react amidation with titanium dioxide through aminosilane coupling agent, combining cysteine and zinc ions to form needle-like nanocrystals, combining physical contact and metal ions to enhance antibacterial properties, and polypeptide through low melting fingers. Propylene, saturated fatty alcohol and maleic anhydride grafted polypropylene as support resins to improve melt flowability and masterbatch compatibility.
Long-term antibacterial properties are achieved, reducing the probability of microbial contamination in drugs and packaging containers, and improving the appearance quality of the bottle caps, avoiding color aberrations and other processing defects.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of polypropylene containers, and in particular to a waterproof and antibacterial medicinal polypropylene bottle cap and a preparation method thereof. Background Art
[0002] As an important part of drug packaging, the design and material selection of bottle caps are crucial to protect drugs from external contamination. Polypropylene, as a common thermoplastic, has been widely used in drug packaging excipients due to its good mechanical strength, chemical corrosion resistance, high thermal stability and waterproof sealing performance.
[0003] In actual use, when patients or medical staff open the bottle cap to take medicine, the surface and inner wall of the bottle cap are easily contaminated by microorganisms from hands and the surrounding environment. Although some existing polypropylene bottle cap products have improved their antibacterial properties by adding antibacterial agents, the antibacterial effect will gradually weaken or even fail after long-term use, and the durability is poor. Summary of the invention
[0004] In order to solve the problem that the current polypropylene bottle caps have poor long-term antibacterial performance, the present application provides a waterproof and antibacterial medicinal polypropylene bottle cap and a preparation method thereof.
[0005] In a first aspect, the present application provides a waterproof and antibacterial medicinal polypropylene bottle cap, the raw material of which contains 1.5-4.7wt% masterbatch, and the balance is polypropylene; the raw material of the masterbatch includes 45-50wt% modified titanium dioxide, 3-5wt% dispersant, and the balance is carrier resin; The preparation method of the modified titanium dioxide is as follows: S1, mixing an aminosilane coupling agent and titanium dioxide in a short-chain alcohol to obtain amino-modified titanium dioxide; S2, adding the amino-modified titanium dioxide to the cysteine solution to carry out an amidation reaction to obtain amidated titanium dioxide; S3. Add the amidated titanium dioxide to the zinc ion solution, stir evenly, then add the cysteine solution, stir for coordination assembly, filter, wash with water, and dry after the reaction is completed.
[0006] Preferably, in step S1, the mass ratio of the aminosilane coupling agent to titanium dioxide is 100:3-6.
[0007] Preferably, in step S2, the concentration of the cysteine solution is 0.05 to 0.2 mol / L, the molar ratio of the cysteine to the aminosilane coupling agent is 1.3 to 2:1, and the amidation reaction time is 30 to 60 minutes.
[0008] Preferably, the temperature of the amidation reaction is 140-160°C.
[0009] Preferably, in step S3, the concentration of the cysteine solution is 0.5-1 mol / L, the concentration of the zinc ion solution is 0.1-0.5 mol / L, and the molar ratio of cysteine to zinc ion is 4-5:1.
[0010] Preferably, the zinc ion solution is selected from at least one of aqueous solutions of zinc nitrate, zinc sulfate and zinc acetate.
[0011] Preferably, in step S3, the coordination assembly time is 10 to 60 minutes, more preferably 20 to 30 minutes.
[0012] Preferably, the cysteine solution is an aqueous solution of cysteine.
[0013] Preferably, the aminosilane coupling agent is selected from one or a combination of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyltriethoxysilane.
[0014] Preferably, the short-chain alcohol is methanol and / or ethanol.
[0015] The modification of the present application is to self-assemble needle-shaped nanocrystals on the surface of titanium dioxide through the coordination of antibacterial metal ions and organic ligands. On the one hand, the needle-shaped nanocrystals can destroy the cell membrane of bacteria through physical contact, achieve good bactericidal function, and have excellent durability and long-term effect; on the other hand, the antibacterial effect of metal ions can be used to inhibit the growth of bacteria. In the above-mentioned modification process, firstly, amino groups are introduced on its surface by the reaction of the hydrolyzate of aminosilane coupling agent with titanium dioxide, and the amidation reaction is carried out by the amino group and the carboxyl group in cysteine, so that cysteine is firmly grafted on the surface of titanium dioxide, which is conducive to improving the durability of the antibacterial function of the obtained needle-shaped nanocrystals. Then, the sulfhydryl, amino and carboxyl groups carried in the cysteine molecule can pre-adsorb metal ions through polarization, provide active sites for the coordination assembly of needle-shaped nanocrystals, and induce MOF crystals to grow on the active sites, thereby forming needle-shaped nanocrystals. It helps to improve the assembly efficiency and the content of MOF crystals and enhance the antibacterial effect when soaking in cysteine solution for the second time.
[0016] In addition, compared with other antibacterial agents, especially metal ion antibacterial agents, this MOF crystal has higher biosafety performance.
[0017] Preferably, the carrier resin comprises low melt index polypropylene, saturated fatty alcohol and maleic anhydride grafted polypropylene in a mass ratio of 30-50:5-10:5-10, and the low melt index polypropylene has a melt index of 1-10 g / 10 min at 190° C. and 2.16 kg.
[0018] Preferably, the saturated fatty alcohol has 8 to 12 carbon atoms.
[0019] Preferably, the saturated fatty alcohol is lauryl alcohol.
[0020] In the present application, titanium dioxide is mainly used as a light-reflecting pigment, and its amount in the masterbatch raw material is relatively large. The increase of its surface roughness and friction resistance after superimposition modification will greatly reduce the extrusion performance of the masterbatch melt extrusion process, increase the residence time and shear stress of the melt in the extruder barrel, and cause defects such as fish eyes, bubbles, and stripes in the masterbatch, and then appearance defects such as color difference appear in the bottle cap processing. To solve this problem, the present application uses a low melt index polypropylene resin to improve the melt fluidity under the premise of ensuring the compatibility of the carrier resin and the polypropylene base resin. In addition, the present application is added with saturated fatty alcohol, which has a significant effect on improving the extrusion problem when the melt enters the die head from the barrel, and effectively alleviates the above-mentioned color difference problem. In addition, the addition of maleic anhydride polypropylene is used to improve the compatibility and solubility of each component of the masterbatch.
[0021] It should be noted that the reason for using the saturated fatty alcohol with carbon atoms of 8 to 12 is that the specified saturated fatty alcohol can gradually migrate to the surface of the bottle cap after extrusion, playing a certain antistatic role, while the saturated fatty alcohol with carbon atoms greater than 12 is usually not easy to migrate. In addition, the preferred lauryl alcohol has relatively good thermal stability.
[0022] Preferably, the dispersant is polyethylene wax.
[0023] Preferably, the titanium dioxide is rutile titanium dioxide.
[0024] Preferably, the D50 particle size of the titanium dioxide is 0.1 to 10 microns, more preferably 0.1 to 0.5 microns.
[0025] The bottle cap and masterbatch raw materials disclosed in the present invention can be added with other processing aids according to the actual processing needs, including but not limited to stabilizers, plasticizers, reinforcing agents, lubricants, flame retardants, antistatic agents, nucleating agents, fillers, and pigments. The amounts used are all conventional amounts, or can be adjusted according to the actual requirements.
[0026] In a second aspect, the present application provides a method for preparing a waterproof sealed medicinal polypropylene bottle cap, comprising the following steps: Prepare raw materials according to any of the above raw material ratios; The masterbatch raw materials are mixed and extruded to obtain masterbatch, and the extruder temperature is set at 180-230°C; The high-density ethylene and masterbatch are hot-melted at 210-225°C and injection-molded into bottle caps.
[0027] In summary, this application has the following beneficial effects: By assembling MOF needle-shaped nanocrystals on the surface of titanium dioxide, a bactericidal effect combining physical and chemical effects can be achieved. In addition, compared with antibacterial agents, the nanocrystals are less likely to fail and can play a long-lasting antibacterial role, effectively reducing the probability of drugs and their packaging containers being contaminated by environmental microorganisms.
[0028] Furthermore, the present application uses low melt index polypropylene, saturated fatty alcohol and maleic anhydride grafted polypropylene as the carrier resin of the masterbatch, which can compensate for the loss of melt extrusion performance caused by a large amount of titanium dioxide and high friction resistance, thereby ensuring the appearance quality of the product. DETAILED DESCRIPTION Preparation Example
[0029] Preparation Example 1, a modified titanium dioxide, the preparation steps are as follows: S1. Take 50g of γ-aminopropyltrimethoxysilane and 1000g of titanium dioxide (D50 is 0.3 micrometers) and add them to ethanol, mix and stir for 30 minutes, filter, wash with water, and dry to obtain amino-modified titanium dioxide.
[0030] S2. Add the amino-modified titanium dioxide into 5 L of cysteine aqueous solution (0.1 mol / L), stir and heat to 160° C. to carry out an amidation reaction for 30 min, separate the precipitate, and obtain amidated titanium dioxide.
[0031] S3. Add amidated titanium dioxide to 2L zinc nitrate aqueous solution (0.3mol / L), stir and react for 20min, add to 4L cysteine solution (0.6mol / L) with stirring, continue stirring and react after the addition is complete, separate the precipitate after 20min, wash with deionized water until neutral, and dry to constant weight.
[0032] Preparation Example 2, a modified titanium dioxide, the preparation steps are as follows: S1. Take 30 g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 1000 g of titanium dioxide (D50 is 0.3 μm) and add them to ethanol, mix and stir for 30 minutes, filter, wash with water, and dry to obtain amino-modified titanium dioxide.
[0033] S2. Add the amino-modified titanium dioxide into 5 L of cysteine aqueous solution (0.1 mol / L), stir and heat to 150° C. to carry out an amidation reaction for 40 min, separate the precipitate, and obtain amidated titanium dioxide.
[0034] S3. Add amidated titanium dioxide to 3L zinc nitrate aqueous solution (0.1mol / L), stir and react for 30min, add to 1.8L cysteine solution (0.8mol / L) with stirring, continue stirring and react after the addition is complete, separate the precipitate after 20min, wash with deionized water until neutral, and dry to constant weight.
[0035] Preparation Example 3, a modified titanium dioxide, the preparation steps are as follows: S1. Take 60g of γ-aminopropyltrimethoxysilane and 1000g of titanium dioxide (D50 is 0.3 micrometers) and add them to ethanol, mix and stir for 30 minutes, filter, wash with water, and dry to obtain amino-modified titanium dioxide.
[0036] S2. Add the amino-modified titanium dioxide into 3.3 L of cysteine aqueous solution (0.2 mol / L), stir and heat to 140° C. to carry out an amidation reaction, react for 50 min, separate the precipitate, and obtain amidated titanium dioxide.
[0037] S3. Add amidated titanium dioxide to 2L zinc nitrate aqueous solution (0.5mol / L), stir and react for 10min, add to 4L cysteine solution (1mol / L) with stirring, continue stirring and react after the addition, separate the precipitate after 30min, wash with deionized water until neutral, and dry to constant weight.
[0038] Preparation Example 4, a modified titanium dioxide, which is different from Preparation Example 1 in that the titanium dioxide is not amino-modified, and the specific preparation steps are as follows: S1. Take 1000g titanium dioxide (D50 is 0.3 microns) and add it to 5L cysteine aqueous solution (0.1mol / L), stir and heat to 160°C, stir and react for 30 minutes, separate the precipitate, and obtain intermediate titanium dioxide.
[0039] S23. Add the intermediate titanium dioxide to 2L of zinc nitrate aqueous solution (0.3mol / L), stir and react for 20 minutes, add to 4L of cysteine solution (0.6mol / L) with stirring, continue to stir and react after the addition is complete, separate the precipitate after 20 minutes, wash with deionized water until neutral, and dry to constant weight.
[0040] Preparation Example 5, a modified titanium dioxide, is different from Preparation Example 1 in that step S2 is not performed. The specific preparation steps are as follows: S1. Take 50g of γ-aminopropyltrimethoxysilane and 1000g of titanium dioxide (D50 is 0.3 micrometers) and add them to ethanol, mix and stir for 30 minutes, filter, wash with water, and dry to obtain amino-modified titanium dioxide.
[0041] S2. Add amino-modified titanium dioxide to 2L zinc nitrate aqueous solution (0.3mol / L), stir and react for 20 minutes, add to 4L cysteine solution (0.6mol / L) while stirring, continue to stir and react after adding, separate the precipitate after 20 minutes, wash with deionized water until neutral, and dry to constant weight. Example
[0042] Example 1, a waterproof and antibacterial medicinal polypropylene bottle cap, the preparation method is as follows: Preparation of masterbatch: 10 kg of raw materials are taken, and the raw material ratio is 47.55% of modified titanium dioxide in Preparation Example 1, 0.53% of antistatic agent (ethoxylated aliphatic alkylamine), 4.16% of polyethylene wax, 6.95% of lauryl alcohol, 34.73% of low melt index polypropylene (Ningbo Formosa Plastics PP1080, melt index is 9g / 10min at 190℃ and 2.16Kg), and 6.08% of maleic anhydride grafted polypropylene (grafting rate 0.8%). The raw materials are added to a high-speed mixer and mixed evenly, and then added to a single-screw extruder for melt extrusion granulation. The temperature of the front section of the extruder is 190-195℃, the temperature of the rear section is 200-215℃, and the temperature of the die head is 220-230℃. After underwater pelletizing, dehydration, drying, and screening, a masterbatch with an average particle size of 2mm is obtained.
[0043] Injection molding: 95.9 kg of polypropylene (Ningbo Formosa Plastics PP1080, melt index 9g / 10min at 190℃ and 2.16 kg) and 4.1 kg of the above masterbatch are melted at 210-225℃, and the melt is injected into the mold and cooled to form. Among them, the temperature of the front section of the extruder is 222℃, the temperature of the middle section is 225℃, the temperature of the back section is 210℃, and the temperature of the nozzle is 220℃.
[0044] Example 2, a waterproof and antibacterial medicinal polypropylene bottle cap, the preparation method is as follows: Preparation of masterbatch: Take 10kg of raw materials, the raw material ratio is 46.27% of modified titanium dioxide in Preparation Example 2, 3.51% of polyethylene wax, 5.60% of lauryl alcohol, 38.37% of low melt index polypropylene (Ningbo Formosa Plastics PP1080, melt index is 9g / 10min at 190℃ and 2.16Kg), and 6.25% of maleic anhydride grafted polypropylene (grafting rate 1.0%). Add the raw materials to a high-speed mixer and mix them evenly, then add them to a single-screw extruder for melt extrusion granulation, the temperature of the front section of the extruder is 190-195℃, the temperature of the rear section is 200-215℃, and the temperature of the die head is 220-230℃. After underwater pelletizing, dehydration, drying, and screening, a masterbatch with an average particle size of 2mm is obtained.
[0045] Injection molding: 98.0kg of polypropylene (Ningbo Formosa Plastics PP1080, melt index 9g / 10min at 190℃ and 2.16Kg) and 2.0kg of the above masterbatch are melted at 210-225℃, and the melt is injected into the mold and cooled to form. Among them, the temperature of the front section of the extruder is 222℃, the temperature of the middle section is 225℃, the temperature of the back section is 210℃, and the temperature of the nozzle is 220℃.
[0046] Example 3, a waterproof and antibacterial medicinal polypropylene bottle cap, the preparation method is as follows: Preparation of masterbatch: Take 10kg of raw materials, the raw material ratio is 47.55% of modified titanium dioxide in Preparation Example 3, 4.16% of polyethylene wax, 6.95% of decanol, 34.73% of low melt index polypropylene (Yanshan Petrochemical K8003, melt index is 2g / 10min at 190℃ and 2.16Kg), and 6.08% of maleic anhydride grafted polypropylene (grafting rate 0.8%). Add the raw materials to a high-speed mixer and mix them evenly, then add them to a single-screw extruder for melt extrusion granulation, the temperature of the front section of the extruder is 180-190℃, the temperature of the rear section is 195-205℃, and the temperature of the die head is 210-225℃. After underwater pelletizing, dehydration, drying, and screening, a masterbatch with an average particle size of 2mm is obtained.
[0047] Injection molding: 95.3kg of polypropylene (Yanshan Petrochemical K8003, melt index 2g / 10min at 190℃ and 2.16Kg) and 4.7kg of the above masterbatch are melted at 210-220℃, and the melt is injected into the mold and cooled to form. Among them, the temperature of the front section of the extruder is 215℃, the temperature of the middle section is 220℃, the temperature of the back section is 210℃, and the temperature of the nozzle is 220℃.
[0048] Example 4, a waterproof and antibacterial medicinal polypropylene bottle cap, is different from Example 1 in that lauryl alcohol is replaced by an equal amount of low melt index polypropylene (Ningbo Formosa Plastics PP1080, melt index of 9 g / 10 min at 190° C. and 2.16 kg).
[0049] Example 5, a waterproof and antibacterial medicinal polypropylene bottle cap, differs from Example 1 in that the maleic anhydride grafted polypropylene is replaced by an equal amount of low melt index polypropylene (Ningbo Formosa Plastics PP1080, melt index of 9 g / 10 min at 190°C and 2.16 kg).
[0050] Example 6, a waterproof and antibacterial medicinal polypropylene bottle cap, which differs from Example 1 in that an equal amount of polypropylene (Formosa Plastics PP5250T, a melt index of 22 g / 10 min at 190°C and 2.16 kg) is used to replace the low melt index polypropylene (Ningbo Formosa Plastics PP1080, a melt index of 9 g / 10 min at 190°C and 2.16 kg). Comparative Example
[0051] Comparative Example 1, a waterproof and antibacterial medicinal polypropylene bottle cap, is different from Example 1 in that the modified titanium dioxide of Preparation Example 1 is replaced by an equal amount of modified titanium dioxide of Preparation Example 4.
[0052] Comparative Example 2, a waterproof and antibacterial medicinal polypropylene bottle cap, is different from Example 1 in that the modified titanium dioxide of Preparation Example 1 is replaced by an equal amount of modified titanium dioxide of Preparation Example 5.
[0053] Comparative Example 3, a waterproof and antibacterial medicinal polypropylene bottle cap, is different from Example 1 in that the modified titanium dioxide of Preparation Example 1 is replaced by unmodified titanium dioxide (D50 is 0.3 μm).
[0054] Comparative Example 4, a waterproof and antibacterial medicinal polypropylene bottle cap, is different from Comparative Example 3 in that the pigment ratio of the masterbatch is 45.55% titanium dioxide, 0.53% antistatic agent (ethoxylated aliphatic alkylamine), 2% zinc ion antibacterial agent, 4.16% polyethylene wax, 6.95% lauryl alcohol, 34.73% low melt index polypropylene (Ningbo Formosa Plastics PP1080, melt index at 190°C and 2.16Kg is 9g / 10min), and 6.08% maleic anhydride grafted polypropylene (grafting rate 0.8%). The following experiments illustrate the beneficial effects of this application: Test 1: Antibacterial performance test of polypropylene bottle caps (1) Referring to the film method in the light industry standard QB / T2591-2003 "Test Methods and Antibacterial Effects of Antibacterial Plastics", the antibacterial rate of the sample for 24 hours was investigated. The test bacteria used were Staphylococcus aureus (ATCC 6538) and Escherichia coli (ATCC 25922). The bottom flat part of the injection-molded polypropylene bottle cap in the above embodiment and comparative example (the smooth outer surface is the test surface) was cut to make a sample (with a diameter of 40 mm), and 5 samples were prepared for each group of samples. The total number of colonies was determined by referring to the counting method of GB / T4789.2-2003. The calculation formula for the antibacterial rate is as follows: R (%) = (BC) / B × 100% Where: R-antibacterial rate, %; B-average number of recovered bacteria in blank control samples, cfu / piece; C- Average number of recovered bacteria in antibacterial plastic samples, cfu / piece.
[0055] (2) Long-term antibacterial performance test Prepare the sample according to the requirements in (1), add it to 500 mL of sterile saline, sterilize it at 120°C, and add 5x10 5 cfu / mL of bacterial solution (the bacterial species is Escherichia coli) was placed at 30°C for 100 days and then the antibacterial rate of the sample was tested again.
[0056] Test 2: Bottle cap color difference test 10 bottle caps were randomly selected from the bottle caps prepared in the examples and comparative examples, and visually inspected for obvious differences in color from the standard bottle caps. All bottle cap samples were qualified if there was no obvious difference in color from the standard bottle caps.
[0057] Table 1. Performance test results
[0058] Combining Examples 1 to 6 and Comparative Examples 3 to 4 and Table 1, it can be seen that, through the scheme of the present application, the modification of titanium dioxide in the present application can significantly improve the long-term antibacterial performance of polypropylene bottle caps. Further, from Comparative Examples 1 to 2, it can be seen that the amino modification and the pre-reaction steps of cysteine and amino groups play a key role in improving the long-term antibacterial performance of the bottle caps. The reason may be that the pre-bonding of cysteine helps to induce the subsequent MOF crystals to grow in specific positions and directions, thereby obtaining needle-shaped nanocrystals with physical bactericidal effects.
[0059] Combining Examples 1 to 3 with Examples 4 to 6 and Table 1, it can be seen that the specific selection of the carrier resin can effectively improve the uniformity of the bottle cap color and reduce the color difference from the standard bottle cap. The reason may be that the specific selected carrier resin can alleviate the negative impact of a large amount of high-friction titanium dioxide on melt fluidity, reduce the quality defects of the masterbatch, and thus ensure the appearance quality of the bottle cap.
[0060] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A waterproof and antibacterial medicinal polypropylene bottle cap, characterized in that: The bottle cap raw material contains 1.5-4.7wt% masterbatch, and the balance is polypropylene; the raw materials of the masterbatch include 45-50wt% modified titanium dioxide, 3-5wt% dispersant, and the balance is carrier resin; The preparation method of the modified titanium dioxide is as follows: S1, mixing an aminosilane coupling agent and titanium dioxide in a short-chain alcohol to obtain amino-modified titanium dioxide; S2, adding the amino-modified titanium dioxide to the cysteine solution to carry out an amidation reaction to obtain amidated titanium dioxide; S3. Add the amidated titanium dioxide to the zinc ion solution, stir evenly, then add the cysteine solution, stir for coordination assembly, filter, wash with water, and dry after the reaction is completed.
2. The bottle cap according to claim 1, characterized in that: In step S1, the mass ratio of the aminosilane coupling agent to titanium dioxide is 100:3-6.
3. The bottle cap according to claim 1, characterized in that: In step S2, the concentration of the cysteine solution is 0.05-0.2 mol / L, the molar ratio of the cysteine to the aminosilane coupling agent is 1.3-2:1, and the amidation reaction time is 30-60 minutes.
4. The bottle cap according to claim 1, characterized in that: In step S3, the concentration of the cysteine solution is 0.5-1 mol / L, the concentration of the zinc ion solution is 0.1-0.5 mol / L, and the molar ratio of cysteine to zinc ion is 4-5:
1.
5. The bottle cap according to claim 1, characterized in that: The aminosilane coupling agent is selected from one or a combination of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyltriethoxysilane.
6. The bottle cap according to claim 1, characterized in that: The carrier resin comprises low melt index polypropylene, saturated fatty alcohol and maleic anhydride grafted polypropylene in a mass ratio of 30-50:5-10:5-10, and the low melt index polypropylene has a melt index of 1-10 g / 10 min at 190° C. and 2.16 kg.
7. The bottle cap according to claim 6, characterized in that: The saturated fatty alcohol has 8 to 12 carbon atoms.
8. The bottle cap according to claim 7, characterized in that: The saturated fatty alcohol is lauryl alcohol.
9. The bottle cap according to claim 1, characterized in that: The dispersant is calcium stearate and zinc stearate in a mass ratio of 1-2:1-2.
10. A method for preparing a waterproof and antibacterial medicinal polypropylene bottle cap, characterized in that: include: Prepare raw materials according to the raw material ratio described in any one of claims 1 to 9; The masterbatch raw materials are mixed and extruded to obtain masterbatch, and the extruder temperature is set at 180-230°C; The high-density ethylene and masterbatch are hot-melted at 210-225°C and injection-molded into bottle caps.
Citation Information
Patent Citations
Antistatic and anti-aging white masterbatch for polypropylene (PP) resin and preparation method thereof
CN102181094A
Titanium dioxide masterbatch and preparation method thereof
CN106905669A
Film-grade polypropylene coloring master batch and preparation method thereof
CN114196110A
Polypropylene antibacterial fiber based on silver-zinc composition and preparation method thereof
CN114293363A
Antiviral bioactive cotton fabric and preparation method thereof
CN116043551A
